The accuracy of ultrasonography in the antenatal diagnosis of placenta accreta in Hospital Universiti Sains Malaysia - Nasir, Mazlin Jamal Abdul (2016)
Objectives The aim of this study is to determine the sensitivity and specificity of ultrasonography in the antenatal diagnosis of placenta accreta in patients with placenta praevia and previous uterine surgery and to compare the morbidity associated with placenta accreta to that of placenta praevia alone. Methodology: This was a retrospective cohort study with the study population consisted of women with diagnosis of placenta praevia with previous uterine surgery, such as Caesarean section(s), dilatation and curettage (D&C), myomectomy or retained placenta who delivered at Hospital Universiti Sains Malaysia between January 2005 and December 2015. The hospital records system was used to identify all patients with the diagnosis of placenta praevia with previous uterine surgery, diagnosed after 28 weeks of gestation. Hospital charts were then traced and reviewed for data collection. The sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of ultrasound in the diagnosis of placenta accreta were calculated. Results: Out of 80 patients included in the study, 15 (18.75%) of them were confirmed to have placenta accreta. The sensitivity and specificity of ultrasound in the diagnosis of placenta accreta were 84.62% and 94.03%, respectively. The positive predictive value (PPV) for ultrasound was 73.33% and the negative predictive value (NPV) was 96.92%. In terms of morbidity, patients with placenta accreta had significant intraoperative blood loss, hysterectomy rate, ICU admission rate, number of packed cells and DIC regime transfusions and longer hospital stay. More neonates in the accreta group required NICU admission. Conclusions: Placenta accreta is associated with significant morbidity compared to placenta praevia alone. Ultrasound is a good diagnostic tool in the diagnosis of placenta accreta. This finding is consistent with other studies.